Effectiveness of reminder sticker books at increasing dental health knowledge and oral hygiene - Muhammad Chair Effendi; Edina Hartami; Merlya Balbeid; Ghea Dewi Hapsari (Universitas Airlangga, 2021)
Background: Health education games can be an effective way for elementary school children to increase their dental health knowledge and oral health. Purpose: This study aims to test the effectiveness of using reminder sticker books by showing the increase in dental health knowledge and improvement in the Simplified Oral Hygiene Index (OHI-S) in seven- to eight-year-olds. Methods: The study was quasi-experimental with a pretest-posttest group design and descriptive analysis method. It involved 54 elementary school students. A reminder sticker book was used to measure the levels of knowledge and oral hygiene. Intraoral examinations were conducted, and the children's frequency of attaching stickers in the morning and afternoon was measured. Frequency was divided into three categories. A questionnaire measured the children's levels of knowledge, which were divided into five categories. Results: The reminder sticker game increased dental health knowledge, with the mean of the control group at 64.4, and the treatment group at 92.5. OHI-S means were 1.68 for the control group and 0.78 for the treatment group. An independent t-test measured the levels of knowledge before and after the study. OHI-S and ANOVA tests measured the increase of dental health knowledge, which was divided into five categories, and decrease in the OHI-S index (divided into three categories). Conclusion: Reminder sticker books can increase oral health knowledge and reduce OHI-S scores in seven- to eight-year-old children.